Rh(ii)-Catalyzed formation of pyrrolo[2, 3-b]quinolines from azide-methylenecyclopropanes and isonitriles. Issue 9 (21st December 2015) - Chen, Kai; Tang, Xiang-Ying; Shi, Min
Abstract : Azide-methylenecyclopropanes underwent an intermolecular cyclization with isonitriles catalyzed by a Rh II complex to produce a series of pyrrolo[2, 3- b ]quinolines in good yields. Moreover, synthetic applications to construct useful heterocycles have also been achieved. Abstract : Azide-methylenecyclopropanes (azide-MCPs) underwent an intermolecular cyclization with isonitriles catalyzed by a Rh II complex to produce a series of pyrrolo[2, 3- b ]quinolines in moderate to good yields via carbodiimide intermediates. Moreover, synthetic applications of these products to construct structurally novel and useful heterocycles have also been achieved.